On the Preparation of Thin Films of Stearyl Methacrylate Directly Photo-Polymerized at the Air-Water Interface - Encina-Rojas, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J (American Chemical Society, 2022)
Characterization of bidimensional polymeric films at the air-water interface in the Langmuir trough, despite being a recurrent topic, usually refers to films of already formed polymeric materials, with very scarce reports on direct polymerization at the air-water interface. In the present work, we studied the photo-polymerization of stearyl methacrylate directly at the air-water interface under a nitrogen atmosphere, with the radical initiator solubilized in the aqueous phase. Two-dimensional (2D) polymerization was monitored by measuring the pressure-area isotherm at different irradiation times. The polymerization leads to a film with an isotherm different from that observed for the monomer, where the surface pressure is directly related to the irradiation time. The shape of this isotherm confirms the presence of a compressed liquid phase, where a higher order can be attained as a consequence of stronger packing forces involving polymer chains. The presence of inter-chain interactions allows rearrangements on the surface of the subphase, and even before the collapse a dense 2D ordering (with a solid phase-like behavior) can be observed. We present a new one-step, solvent-free procedure to obtain a photo-polymeric film directly at the air-water interface, which can be transferred to a solid surface by the Langmuir-Blodgett method, allowing film preparation of controlled thickness. Films were characterized by measuring properties such as thickness, roughness, and hydrophobicity and comparing them with films obtained from a conventional polymer. We report the differences between the interfacial behavior of amphiphilic molecules and nanomaterials such as films obtained by photo-polymerization, PSMA, directly on the air-water interface. © 2022 American Chemical Society.